Recent advances and industrial viewpoint for biological treatment of wastewaters by oleaginous microorganisms. (May 2017) - Huang, Chao; Luo, Mu-Tan; Chen, Xue-Fang; Xiong, Lian; Li, Xiao-Mei; Chen, Xin-De
Highlights: Biological treatment of wastewaters by oleaginous microorganisms is reviewed. The potential of industrialization of this technology is discussed. The issues for the industrial application of this technology are presented. Critical outlook for development of this technology is given. Abstract: Recently, technology of using oleaginous microorganisms for biological treatment of wastewaters has become one hot topic in biochemical and environmental engineering for its advantages such as easy for operation in basic bioreactor, having potential to produce valuable bio-products, efficient wastewaters treatment in short period, etc. To promote its industrialization, this article provides some comprehensive analysis of this technology such as its advances, issues, and outlook especially from industrial viewpoint. In detail, the types of wastewaters can be treated and the kinds of oleaginous microorganisms used for biological treatment are introduced, the potential of industrial application and issues (relatively low COD removal, low lipid yield, cost of operation, and lack of scale up application) of this technology are presented, and some critical outlook mainly on co-culture method, combination with other treatments, process controlling and adjusting are discussed systematically. By this article, some important information to develop this technology can be obtained.